Pengembangan Modul Matematika Dengan Strategi Problem Solving Untuk Mengukur Tingkat Kemampuan Berpikir Kreatif Matematis Siswa Di SMP Muhammadiyah Kupang - Asa, Ela Marsela; Zulfikar, Ryan Nizar; Syarief, Nur Hasanah (Program Studi Pendidikan Matematika, Universitas Muhammadiyah Kupang, 2023)
The objectives of this study were to discover the development of mathematics modules with problem-solving strategies to assess students' mathematical creative thinking abilities, and also to describe teachers' and students' reactions to the development of mathematics modules with problem-solving strategies to assess students' mathematical creative thinking abilities. The method used in this study is Research and Development (R&D), which includes stages such as define, design, develop, and disseminate. In this study, data was collected through a validation questionnaire administered by material and media specialists, as well as small group trials and teacher response surveys.Based on the results of stage I validation by the experts, a cumulative average score of 4.08%